Ice-Ship Collision in the Arctic Region - Chen, Chi (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2015)
As the global warming enhance the ice melting in the Arctic region, it is easier to access the area once thought to be the forbidden zone for human beings. The shipping and offshore industry can have a lot benefits from the Arctic region. The Euro-Asian shipping route is shorter via the Arctic than traditional Suez Cannel Route. Furthermore, according to the data reported by the US Geological Survey, over one tenth of the undiscovered oil and around one third of the undiscovered natural gas reserves are believed to be stored in the Arctic region. There is a huge potential for the energy exploration in the Arctic. Due to the public concerns regarding the safety and environmental sensitive in this region, sailing and operation in the Arctic region has been attracted increasing attention. In marine industry, great challenge can also come from the technical immaturity related to the icebergs and low temperature effects, which are the major threats to the safe vessel operating in the Arctic region. The iceberg with huge inertia can cause serious damage on vessels' structure if there is a collision happened between the ship and iceberg even though the ice is considered to be fragile. The low temperature can contribute to a higher steel yield stress but also lead to be brittle characteristics. The steel will have lower failure strain value due to low temperatures. In addition to these factors, the consequence of an ice-ship collision may be affected by other factors like the shape of the iceberg, boundary conditions, collisions etc. In order to have a detail investigation into the collision in the Arctic region, FE simulation is implemented in this thesis project. It is expected that the collision will lead to non-linear deformation of the metal structure. The explicit simulation method is used to model the collision phenomena. The simulation is carried out by the FE software ANSYS Workbench Explicit using the dynamic explicit solver of AUTODYN. Many cases are raised in this thesis report to conclude the factors that ...